Roles of Surgery in the Treatment of Patients With High-Risk Neuroblastoma in the Children Oncology Group Study: A Systematic Review and Meta-Analysis - Qi, Yingyi; Zhan, Jianghua (Frontiers in Pediatrics, 2021)
Purpose Neuroblastoma is the most common extracranial solid tumor in children, and most patients are at high risk when they are initially diagnosed. The roles of surgery and induction chemotherapy in patients with high-risk neuroblastoma have been a subject of much controversy and debate. The objective of the current study was to assess the roles of surgery in high-risk neuroblastoma. Method The review protocol was prospectively registered (PROSPEROID: CRD42021253961).The Pubmed, Embase, Cochrane, and CNKI databases were searched from inception to January 2020 with no restrictions on language or publication date. Clinical studies comparing the outcomes of different surgical ranges for the treatment of high-risk neuroblastoma were analyzed. The Mantel-Haenszel method and a random effects model was utilized to calculate hazard ratio (95% CI). Results Fourteen studies that assessed 1915 subjects met full inclusion criteria. Compared with gross tumor resection(GTR) group, complete tumor resection(CTR) did not significantly improve the 5-year EFS (p=1.0; HR = 0.95[95% CI, 0.87to 1.05]; I2=0%), and 5-year OS (p=0.76; HR = 1.08[95% CI, 0.80to 1.46]; I2=0%) of patients. GTR or CTR resection had significantly better 5-year OS (p =0.45; HR = 0.56[95% CI, 0.43to 0.72]; I2=0%) and 5-year EFS(p =0.15; HR = 0.80[95% CI, 0.71to 0.90];I2=31%)than subtotal tumor resection(STR) or biopsy only, however both CTR or GTR showed a trend for more intra and post operative complications compared to the STR or biopsy only (p=0.37;OR=1.54[95%CI,1.08to2.20];I2=0%). The EFS of the patients who underwent GTR or CTR at the time of diagnosis and after induction chemotherapy were similar (p=0.24;HR=1.53[95% CI, 0.84to 2.77]; I2=29%). Conclusion: For patients with high-risk neuroblastoma, complete tumor resection and gross tumor resection of the primary tumor were related to improved survival, with very limited effects on reducing intraoperative and postoperative complications. It is necessary to design strong chemotherapy regimens to improve the survival rate of advanced patients.